High Clostridium difficile contamination rates of domestic and imported potatoes compared to some other vegetables in Slovenia. (April 2019) - Tkalec, Valerija; Janezic, Sandra; Skok, Barbara; Simonic, Tamara; Mesaric, Simon; Vrabic, Tanja; Rupnik, Maja
Abstract: Clostridium difficile, recently reclassified to Clostridioides difficile, is among most important causes of intestinal infections in humans. Zoonotic potential and foodborne transmissions are considered to be partially involved in C. difficile spread. Here we report prevalence of C. difficile in 142 retail and 12 homegrown vegetables in Slovenia between years 2014 and 2017. The overall prevalence of C. difficile on vegetables was 18, 2% (28/154). A total of 115 isolates were obtained which belonged to 25 PCR ribotypes. Ten of those were toxigenic and PCR ribotype 014/020 was the most prevalent. Most of 25 determined PCR ribotypes were previously reported in humans, animals, soil or water in Slovenia. Among tested vegetables, potatoes had the highest positivity rate (28, 0% vs. 6, 7% and 9, 4% for ginger and leaf vegetables). Altogether 66, 7% of C. difficile positive potato samples were imported from 12 different countries of three different continents. The origin of contamination could be any point between production and retail store, however, our results suggest a possibility that potatoes represent a transnational and transcontinental way of C. difficile transmissions. Highlights: C. difficile was detected in 28 out of 154 (18, 2%) vegetable samples. Potatoes exhibited higher positivity rate than ginger and leaf vegetables. Found ribotypes were diverse and substantially overlapped with other reservoirs. Vegetable, especially potatoes, may be a transcontinental way of C. difficile spread.